Metro Manila environment problem and perspective - Philippines. Environmental Management Bureau. Environmental Education and Information Division ([S.l.] Megascope Graphics)
Discusses and shows the different environmental problems surrounding Metro Manila, i.e., pollution, flooding, slums and squatters, degradation of natural resources; and the plan to implement the environmental improvement program.
VHS
Keywords: Pollution -- Environmental aspects -- Philippines -- Metro Manila; Environmental health -- Philippines -- Metro Manila; Pollutants -- Philippines -- Metro Manila; Environmental science